Coral health levels of wild ornamental coral in East Belitung waters, Indonesia - OFRI JOHAN; RENDY GINANJAR; AGUS PRIYADI (Nusantara Bioscience, 2015)
Abstract. Johan O, Ginanjar R, Priyadi A. 2015. Coral health levels of wild ornamental coral in East Belitung waters, Indonesia. Nusantara Bioscience 7: 133-138. The distribution of coral diseases has been reported in waters having coral reef in the world including Indonesia, but there had been no report from East Belitung, Indonesia. This study was conducted on 25 March 2014 and on 26-27 April 2014 in nine locations, offshore of Belitung, namely in the Islands of Memperak, Bakau, Buku Limau, Pesambung, Muranai, Sembilan, Berlian, Tempuling, and Gresik. The objective of this study was to distinguish the levels of ornamental coral health due to infection and other coral health compromises. Data were collected using line transect method to estimate coral cover condition and using belt transect method to estimate coral disease prevalence. The results showed that the Black Band Disease (BBD), White Syndrome (WS), and Skeleton Eroding Band (SEB) were the main diseases, while the coral health compromisers were competition among coral, algae, sedimentation and pigmentation response. This is the first report of SEB disease from East Belitung, while other diseases have been found frequently. The prevalence of diseases was categorized as normal, and so, no management intervention is needed.